Forkert nummer - Telefonen som ledemotiv i Botho Strauß’ forfatterskab og slægtskabet med den pessimistiske teknologitænkning - Schiølin, Kasper (Passage - Tidsskrift for litteratur og kritik, 2014)
Kasper Schiølin: “Wrong Number: The Telephone as a Leitmotif in the Work of Botho Strauß and the Affinity with the Pessimistic Philosophy of Technology” The article explores the telephone as a central leitmotif in the writings of German author Botho Strauß. It stresses that Strauß in different ways deliberately ‘short-circuits’ the phone, so that it does not facilitate meaningful communication but only increases loneliness and despair. The last part of the article shows how this artistic inversion of the phone becomes a questioning of technology, corresponding to the technological pessimism of early philosophy of technology.